2016
DOI: 10.1175/jpo-d-15-0155.1
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Variance Budgets of a Diffusive Staircase with Implications for Heat Flux Scaling

Abstract: The steady-state energy and thermal variance budgets form the basis for most current methods for evaluating turbulent fluxes of buoyancy, heat, and salinity. This study derives these budgets for a double-diffusive staircase and quantifies them using direct numerical simulations; 10 runs with different Rayleigh numbers are considered. The energy budget is found to be well approximated by a simple three-term balance, while the thermal variance budget consists of only two terms. The two budgets are also combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…This energy input of C. okenii is converted into an increase of the system's potential energy, dE p /dt, or it is dissipated into heat by friction. Two more contributions to the energy balance (dE k /dt and D V , supporting information Text S4 [Hieronymus and Carpenter, 2016;Winters et al, 1995]) were found negligible. At t = 10 h, when the mixed layer thickness in the simulation reached 0.3 m, as measured in Lake Cadagno, the mean dissipation rate ε within the C. okenii layer was (1.0 ± 1.5) × 10 À10 W kg À1 , or 42% of the bacterial energy input rate R = 2.4 × 10 À10 W kg À1 .…”
Section: 1002/2017gl074868mentioning
confidence: 90%
“…This energy input of C. okenii is converted into an increase of the system's potential energy, dE p /dt, or it is dissipated into heat by friction. Two more contributions to the energy balance (dE k /dt and D V , supporting information Text S4 [Hieronymus and Carpenter, 2016;Winters et al, 1995]) were found negligible. At t = 10 h, when the mixed layer thickness in the simulation reached 0.3 m, as measured in Lake Cadagno, the mean dissipation rate ε within the C. okenii layer was (1.0 ± 1.5) × 10 À10 W kg À1 , or 42% of the bacterial energy input rate R = 2.4 × 10 À10 W kg À1 .…”
Section: 1002/2017gl074868mentioning
confidence: 90%
“…Estimates of heat and salt fluxes can be made by considering the steady state energy balance for a layer (e.g., Hieronymus & Carpenter, ): ϵ=gαFθgβFS, which relates the dissipation of turbulent kinetic energy ϵ within a layer and the net buoyancy flux for large Rayleigh numbers (Rayleigh numbers are 108 for the Canada Basin layers; Shibley et al, ). Note that assumes that there is no large‐scale background shear which is a reasonable assumption given that the lateral density gradient in the Canada Basin at these depths is effectively 0.…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…The second method for estimating vertical diffusive heat fluxes F H ε is based on measured ε and assumes mechanical energy conservation (i.e., potential plus kinetic energy) within the double‐diffusive layers (Hieronymus and Carpenter ). The buoyancy flux J int through a double‐diffusive interface is equal to the dissipation rate ε within the mixed layer plus a diffusive buoyancy flux J d within the mixed layer (for derivation see Hieronymus and Carpenter []): Jint=ε+Jd …”
Section: Methodsmentioning
confidence: 99%
“…The ratio γ H ≡ J d / J int of the two buoyancy flux terms is ~ 0.20 for a mixed‐layer‐based Rayleigh number of ~ 10 8 typical for Lake Kivu (Sommer et al ; Hieronymus and Carpenter ). Using this definition for γ H leads to a relation to the measured dissipation ε by Jint=ε1γH …”
Section: Methodsmentioning
confidence: 99%